Terminação de cordeiros suplementados em pastagem de tifton-85 ou confinados com dieta de alto grão - Simões, Fernanda de Souza Britto (2015)
This study was conducted at Sheep Laboratory of the Federal University of Santa Maria (UFSM), and to evaluate nutrient intake, performance, feeding behavior, the quantitative and qualitative characteristics of Tifton-85 pasture (Chapter I) as well as carcass characteristics, tissue composition and non-carcass of lambs weaned constituents finished in different feeding systems (Chapter II). Twenty-six male, weaned, castrated lambs cross-bred from Texel and Ile de France breeds were used. The treatments were the following: T1 - Containment: Concentrate + Tifton 85 hay (ad libitum) (CONF); T2 - Tifton-85 pasture + concentrate (ad libitum) (PSA) and T3 - Tifton-85 pasture + concentrate (1.0% body weight) (PSR). The animals were slaughtered when they reached the body condition (BC) pre-established 3.0. The consumption, performance, feeding behavior, carcass characteristics, the commercial cuts and non-carcass of the lambs were influenced (P<0.05) by different feeding systems. In treatments where the energy level in the diet was higher (CONF and PSA) animals showed DM, OM and CP higher, but lower NDF (P<0.05). Performed better (P<0.05). But the feeding behavior of the parameters of the lambs have changed (P<0.05) through the lower intake of NDF, but without compromising the rumination activity. Also showed superiority (P <0.05) on carcass traits, heavier commercial cuts (P<0.05) and the least developed gastrointestinal tract (P<0.05) compared to the lambs of PSR. However, the body measurements in vivo and on carcass, the tissue composition of the palette and the quantitative and qualitative characteristics of Tifton-85 pasture were not affected (P>0.05) by different systems terminus, except for the conformation and leg width (P<0.05) in lambs PSR. Thus, the confinement, the pasture with supplementation ad libitum or restricted characterized as viable alternatives of technical and productive point of view for finishing lambs weaned. Introducing potential for production carcasses with excellent quality, meeting the demands of actual consumer market.